63. Validation of names of some syntaxa of the Crimean vegetation - Didukh, Yakiv P.; Mucina, Ladislav (Lazaroa, 2014)
We validate concepts and names of three alliances (Androsaco tauricae-Caricion humilis, Adonido vernalis-Stipion tirsae, Veronico multifidae-Stipion ponticae) of steppe vegetation (Festuco-Brometea) of Crimea as well as two other alliances of sub-mediterranean character (Diantho humilis-Velezion rigidae, Elytrigio nodosae-Rhuion coriariae). We also validatea number of associations, most of them to serve as the holotypes of the alliances.